2019
DOI: 10.32819/2019.71015
|View full text |Cite
|
Sign up to set email alerts
|

Dependending of biochemical activities Mycobacterium bovis on passages and temperature of cultivation

Abstract: The tuberculosis of cattle remains a serious problem both in Ukraine and for the whole world for many years. In spite of the fact that in science now much known about the agent of tuberculosis, some of the mechanisms through which mycobacteria manage to survive in the conditions of macroorganism and the environment have not been studied. Difficulties in overcoming of tuberculosis and mycobacteriosis can be connected with the incredible plasticity of life processes within the bacterial cells of mycobacteria. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…During the study of biochemical activity, we identified the catalase, peroxidase, dehydrogenase activities, presence of reduction of nitrates, and ability to hydrolize Tween 80. Catalase and peroxidase activities were identified using the modified Bogen's technique (Tkachenko et al, 2019). Into test tubes with the culture, we added 2% solution of hydrogen peroxide and 0.5% solution of pyrogallol A.…”
Section: Ethicalmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study of biochemical activity, we identified the catalase, peroxidase, dehydrogenase activities, presence of reduction of nitrates, and ability to hydrolize Tween 80. Catalase and peroxidase activities were identified using the modified Bogen's technique (Tkachenko et al, 2019). Into test tubes with the culture, we added 2% solution of hydrogen peroxide and 0.5% solution of pyrogallol A.…”
Section: Ethicalmentioning
confidence: 99%
“…The studies of dehydrogenase activity were carried out using the Bloch technique (1950), modified by Tkachenko et al (2019). We gathered 4.0 cm 3 of weighed amount of the culture of microbial cells with the concentration of 10.0 mg/cm 3 in phosphate buffer (рН 7.4-7.6), mixed with 1.0 cm 3 of 1.0% of glucose solution and 0.1 cm 3 of 0.02% solution of methylene blue.…”
Section: Ethicalmentioning
confidence: 99%
See 1 more Smart Citation